Investigation of the Anti-Leishmania (Leishmania) infantum Activity of Some Natural Sesquiterpene Lactones - Wulsten, Imke; Costa-Silva, Thais; Mesquita, Juliana; Lima, Marta; Galuppo, Mariana; Taniwaki, Noemi; Borborema, Samanta; Da Costa, Fernando; Schmidt, Thomas; Tempone, Andre (Molecules (Basel, Switzerland), 2017)
Leishmaniases are neglected infectious diseases caused by parasites of the ‘protozoan’ genus Leishmania. Depending on the parasite species, different clinical forms are known as cutaneous, muco-cutaneous, and the visceral leishmaniasis (VL). VL is particularly fatal and the therapy presents limitations. In the search for new anti-leishmanial hit compounds, seven natural sesquiterpene lactones were evaluated against promastigotes and intracellular amastigotes of Leishmania (Leishmania) infantum, a pathogen causing VL. The pseudoguaianolides mexicanin I and helenalin acetate demonstrated the highest selectivity and potency against intracellular amastigotes. In addition, promastigotes treated with helenalin acetate were subject to an ultrastructural and biochemical investigation. The lethal action of the compound was investigated by fluorescence-activated cell sorting and related techniques to detect alterations in reactive oxygen species (ROS) content, plasma membrane permeability, and mitochondrial membrane potential. Helenalin acetate significantly reduced the mitochondrial membrane potential and the mitochondrial structural damage was also confirmed by transmission electron microscopy, displaying an intense organelle swelling. No alteration of plasma membrane permeability or ROS content could be detected. Additionally, helenalin acetate significantly increased the production of nitric oxide in peritoneal macrophages, probably potentiating the activity against the intracellular amastigotes. Helenalin acetate could hence be a useful anti-leishmanial scaffold for further optimization studies.